Preparation and Microwave-Absorbing Property of Solid-Waste-Derived Ceramic Foam - Zheng Wang; Minghao Mu; Xinqiang Liu; Congcong Jiang (Crystals)
Recently, electromagnetic wave (EMW)-absorbing materials have obtained increasing attention for both military and civil applications. This study adopted the powder sintering method and the concept of recycled wastes in fabricating functional ceramic foam (CF). Firstly, a ceramic green body composed of pulverized granite residues, waste glass, and a foaming agent was sintered. The influence of the sintering temperature and SiC addition on CF was investigated, and then surface graphitization post-treatment of CF was performed as well. The truly enhanced compressive strength and EMW-absorbing property of surface graphitization ceramic foam (SG-CF) with a homogeneous porous structure was realized in the present work, which is promising as a candidate in EMW absorption systems.